Waste not, want not: Putting urban metabolism into practice - Aiu, Imaikalani. (2017)
Abstract: Urban Metabolism is a promising analytical method for sustainability planning. There exist several robust tools and analytical methods as well as related disciplines to comprehensively carry out the practice and address the social, environmental and economic dimensions of sustainability. Yet in North America, no urban municipality has used urban metabolism in sustainability planning. Despite the aim of many cities to be sustainable, very few planning documents reflect systemic or "strong sustainability." In order for the urban metabolism practice to bridge this gap there must be greater outreach by professionals, advocacy on national levels, adoption of standards, and application on specific issue municipal plans.; Thesis (M.A.)--Tufts University, 2016.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Sheldon Krimsky.; Committee: Julian Agyeman.; Keyword: Urban planning.